Analysis of information and financial flows for the operation of insurance companies - Конохова, Юлия Валерьевна (Eastern-European Journal of Enterprise Technologies, 2011)
The paper is devoted to giving general characteristic of the environment of functioning of the insurance company, to analyze the process of insurer’s capital formation, identified internal and external factors that influence this process